RUMPON ATRAKTOR IJUK UNTUK PERIKANAN REKREASI DI KABUPATEN ACEH JAYA PROVINSI ACEH - Hafinuddin Hafinuddin; Muhammad Arif Nasution; Muhammad Agam Thahir; Ikhsanul Khairi (Universitas Teuku Umar, 2020)
The traditional fish aggregating devices (FADs) have been assist fishing gear i.e. surface gill nets and hand lines to catching pelagic fish. The traditional FADs have been used by partners of fishermen in Aceh Jaya District and that is increased operational/maintenance costs and decreased fishermen's profits. In addition, areca leaves or coconut leaves are increasingly difficult to obtain. Therefore, the palm fiber FAD technology is expected to be able to increase fishermen's income and satisfaction for community who catch fish for fishing recreation or fishing sport. The approach to solving problems was carried out with education, training and mentoring. This community partnership program (PKM) activity was carried out from January to March 2020. The output of PKM activities is to increasing knowledge and skills for fishing communities. In addition, applied of palm fiber FADs can be better than traditional FADs and can be effect to fisherman’s income of recreational fisheries.